Social Cognitive Dysfunction in Elderly Patients After Anesthesia and Surgery - Zhang, Delin; Ying, Jun; Ma, Xiaochi; Gao, Zaifeng; Chen, Hanjian; Zhu, Shengmei; Shi, Liping; Lu, Xiqian (Frontiers in Psychology, 2020)
Extensive studies have revealed that cognitive processing was impaired after anesthesia and surgery, particularly for the elderly patients. However, most of the existing studies focused on the general cognitive deficits (e.g., delayed neuro-cognitive recovery and POCD). Although diagnosis of social abilities has been used in various clinical fields, few studies have investigated the potential deficit on social cognition after anesthesia and surgery. The current study examined whether there was any social cognitive dysfunction after anesthesia and surgery. We achieved this by taking biological motion as the stimuli of interest, the perception of which has been taken as the hallmark of social cognition. The elderly patients (aged >=60 years) were required to judge whether an upright biological motion stimulus appeared among the dynamic noises to test their social cognition, as well as do a Mini-Mental State Examination to test their general cognition. The two tests were performed at both 1-day before and 7-day after the surgery. Results showed that 31.25% of patients exhibited BM perception deficit after anesthesia and surgery relative to before anesthesia and surgery, implying that social cognitive dysfunction existed. Meanwhile, social cognitive dysfunction was independent from delayed neurocognitive recovery.